DFT Study on Adiabatic and Vertical Ionization Potentials of Graphene Sheets - Igor K. Petrushenko (Advances in Materials Science and Engineering)
Adiabatic and vertical ionization potentials (IPs) of finite-size graphene sheets as a function of size were determined by using density functional theory. In the case of graphene a very moderate gap between vertical and adiabatic IPs was observed, whereas for coronene molecule as a model compound these values differ considerably. The ionization process induces large changes in the structure of the studied sheets of graphene; “horizontal” and “vertical” bond lengths have different patterns of alternation. It was also established that the HOMO electron density distribution in the neutral graphene sheet affects its size upon ionization. The evolution of IPs of graphene sheets towards their work functions was discussed.